“Two-Cell Assemblage” Assay: A Simple in vitro Method for Screening Hair Growth-Promoting Compounds - Jang, Sunhyae; Ohn, Jungyoon; Kang, Bo Mi; Park, Minji; Kim, Kyu Han; Kwon, Ohsang (Frontiers in Cell and Developmental Biology, 2020)
Alopecia arises due to inadequate hair follicle (HF) stem cell activation or proliferation, resulting in prolongation of the telogen phase of the hair cycle. Increasing therapeutic and cosmetic demand for alleviating alopecia has driven research towards the discovery or synthesis of novel compounds that can promote hair growth by inducing HF stem cell activation or proliferation and initiating the anagen phase. Although several methods for evaluating the hair growth-promoting effects of candidate compounds are being used, most of these methods are difficult to use for large scale simultaneous screening of various compounds. Herein, we introduce a simple and reliable in vitro assay for the simultaneous screening of the hair growth-promoting effects of candidate compounds on a large scale. In this study, we first established a 3D co-culture system of human dermal papilla cells and human outer root sheath cells in an ultra-low attachment 96-well plate, where the two cell types constituted a polar elongated structure, named "two-cell assemblage (TCA)". We observed that the long axis length of the TCA gradually increased for five days, maintaining biological functional integrity as reflected by the increased expression levels of hair growth-associated genes after treatment with hair growth-promoting molecules. Interestingly, the elongation of the TCA was more prominent following treatment with the hair growth-promoting molecules (which occurred in a dose-dependent manner), compared to the control group (p < 0.05). Accordingly, we set the long axis length of the TCA as an endpoint of this assay, using a micro confocal high-content imaging system to measure the length, which can provide reproducible and reliable results in an adequate timescale. The advantages of this assay are: i) it is physiologically and practically advantageous as it uses 3D cultured two-type human cells which are easily available; ii) it is simple as it uses length as the only endpoint; iii) it is a high throughput system, which screens various compounds simultaneously. In conclusion, the “TCA” assay could serve as an easy and reliable method to validate the hair growth-promoting effect of a large volume of library molecules.